PARASITES IDENTIFICATION ON CORAL GROUPER (Plectropomus reolatus) IN FLOATING NET CAGE IN PAGIMANA SUB-DISTRICT OF BANGGAI REGENCY - Agustina, Sri Sukari (Jurnal Harpodon Borneo, 2017)
This research was conducted to know the kinds of parasites that attack of coral grouper (Plectropomus reolatus) in floating net cage in Pagimana Sub-district of Banggai Regency. The technique of collecting data of grouper in floating net cage in Jayabakti Village and Samajatem Village, Pagimana Sub-district is done randomly (Random Sampling), while for laboratory analysis is done at Station KIPM Class II Luwuk Banggai. The sample of grouper taken in the form of live fish in a state of almost died / collapse. Parasitic examination includes morphological observation, behavior, ectoparasite examination and endoparasit examination. The results of the identification of parasite that attacked of coral grouper (Plectropomus reolatus) on floating net cage in Pagimana subdistrict of Banggai Regency showed that the parasite species that attacked of coral grouper were Oodinium sp, Benedenia sp, Trichodina sp, Chilodonella spp, and Crepidostomum sp. Keywords : parasites, floating net cage, Plectropomus reolatus